‘Step into her World’: Including the Voices of Learning-Disabled Children and Young People in Research - Diana Fields; Laura Fox; Kathryn Asbury (International Journal of Qualitative Methods, 2025)
The voices of learning-disabled children and young people are rarely heard in qualitative research, particularly when they have complex communication needs. The current study was motivated by a desire to identify and co-produce effective and ethical qualitative research methods that would be capable of supporting the inclusion of this group of children and young people. We interviewed 12 parents of children with chromosomal learning disabilities and 6 professionals working with learning-disabled children, and we also observed 9 learning-disabled children and young people in classroom settings in order to develop methodological recommendations. Transcripts and field notes from these ( n = 27) interviews and observations were analysed using Template Analysis, supplemented with reflexive Thematic Analysis. We identified ideas regarding the most effective communication and data collection strategies for this group; thoughts on the challenges to including learning-disabled voices in research; ethical considerations and the characteristics and experience required to be an effective researcher in this area. There was a good consensus that it would be highly valuable to develop more innovative and inclusive qualitative research methods for this group of people, and that it is vital that a careful, ethical and co-produced approach is taken to this endeavour. The next step will be to use these proposals to explore the issue with learning-disabled children and young people themselves.